Effect of Step Height on the Aeration Efficiency of Cascade Aerator System Using Particle Image Velocimetry - Azman A.; Zawawi M.H.; Hassan N.H.; Abas A.; Razak N.A.; Mazlan A.Z.A.; Mohd Remy Rozainy M.A.Z. (EDP Sciences, 2023)
Air entrainment; Efficiency; Flow visualization; System theory; Velocimeters; Velocity measurement; Water aeration; Water filtration; Aeration efficiencies; Laboratory studies; Mass flow rate; Particle image velocimetries; Physical model; Turbulence effect; Velocity profiles; Water filtration systems; Water treatment